Has high-tech cluster improved regional innovation capacity? evidence from Wuhan metropolitan area in China - Bao, Jinhong; Li, Yin (Frontiers in Environmental Science, 2023)
High-tech industries are the key driving force to improving regional innovation.Studying the relationship between high-tech clusters and regional innovation capacity helps optimize the spatial layout of regional high-tech industries, upgrade the industrial structure and enhance regional innovation capacity. Based on the panel data of nine cities in the Wuhan Metropolitan Area from 2010-2019, we measure the regional innovation capacity and the degree of high-tech cluster using the super-SBM and locational quotient. Furthermore, we explore the high-tech cluster's influence on regional innovation capacity by constructing a non-linear panel threshold model and a spatial econometric model. The results showed: (1) The innovation capability of the Wuhan Metropolitan Area shows a "W" type fluctuation upward trend, and the degree of the high-tech cluster is below the quotient level of 1, showing a continuous "M" type trend; (2) There is a non-linear double-threshold effect between high-tech cluster and innovation capacity, and the overall effect of promotion, but there is a marginal decreasing, probably because of the crowding effect or over-competition of the high-tech cluster in some regions; (3) After considering the spatial effect, the impact of the high-tech cluster on the innovation capacity of both local and neighboring regions shows a "U" curve, but the spillover to the neighboring areas is relatively limited. Therefore, to give full play to the advantages of the high-tech cluster, it is necessary to take a long-term view when formulating relevant industrial policies while considering the differences in regional economic development levels and spatial spillover effects.